The Role of Legal Consultants Conducting Legal Due Diligence on Corporate Actions to Establish Joint Venture Legal Entities in the Matter of Foreign Investment (PMA) - Abraham Astral Rantesalu (Formosa Journal of Multidisciplinary Research, 2022)
Formation of a Joint Venture which can be said as a joint venture has its own uniqueness. This uniqueness can be found because there is involvement of foreign parties who invest in Indonesia either as individuals or foreign legal entities. This joint venture company was established in the form of a Limited Liability Company, which is subject to Law Number 40 of 2007 concerning Limited Liability Companies. Before forming a Joint Venture Company, the parties first make a joint venture agreement which forms the basis for establishing a joint venture company. In formulating a joint venture agreement, the parties are bound by the principles contained in contract law, both national and international, such as pacta sunt servanda, consensus, and freedom of contract, because the parties come from different countries. There are many parameters and benchmarks which must be a reference for legal consultants, especially in carrying out Legal Aspect Due Diligence and making Legal Opinions for these clients in order to minimize and find out what risks can legally impact the activities to be carried out by these clients.